2018
DOI: 10.1097/cej.0000000000000320
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spirogyra neglecta on the early stages of 1, 2-dimethylhydrazine-induced colon carcinogenesis in rats

Abstract: This study focused on the chemopreventive effects of Spirogyra neglecta extract (SNE) and dried S. neglecta mixed diet on the early stages of 1,2-dimethylhydrazine (DMH)-induced colon carcinogenesis in rats. Male Wistar rats were injected with DMH to initiate aberrant crypt foci (ACF) formation. In the initiation stage, SNE significantly decreased the number of ACF in the colon of DMH-treated rats. Rats that received a low dose of SNE showed enhanced activity of several detoxifying and antioxidant enzymes. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…During colorectal cancer progression, survivin obviously has the dual function of preventing tumor cell apoptosis and controlling the cell-cycle proliferation. This peculiarity concurs to both accelerate proliferative activity and suppress apoptosis [27-28]. High survivin expression has been observed in various types of tumors and therefore may represent a promising drug target for tumor treatment [29].…”
Section: Discussionmentioning
confidence: 99%
“…During colorectal cancer progression, survivin obviously has the dual function of preventing tumor cell apoptosis and controlling the cell-cycle proliferation. This peculiarity concurs to both accelerate proliferative activity and suppress apoptosis [27-28]. High survivin expression has been observed in various types of tumors and therefore may represent a promising drug target for tumor treatment [29].…”
Section: Discussionmentioning
confidence: 99%
“…S. neglecta alga was previously reported for its antioxidant, anti-bacterial and anti-inflammatory properties [ 22 , 23 , 36 , 37 ]. Regarding anti-cancer properties, S. neglecta water extract demonstrated in vivo cancer chemopreventive effects on DEN-induced hepatocarcinogenesis [ 25 ] as well as on the management of early stages of colon carcinogenesis in rat models [ 26 ]. In our previous study, using the plant-based metabolomic profiling technique, the S. neglecta ethyl acetate fraction inhibited PC3 prostate cancer cell metastasis via the inhibition of Akt/MAPK signaling pathway [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the water extract of S. neglecta showed a protective effect against diethylnitrosamine-induced hepatocarcinogenesis in rats [ 25 ]. S. neglecta extract also inhibited the early stages of DMH-induced colon carcinogenesis in rats by modulating xenobiotic metabolizing enzymes, inhibition of cell proliferation, and induction of apoptosis [ 26 ]. In our previous study, we found that the ethyl acetate fraction of S. neglecta inhibited the metastasis of PC3 prostate cancer cells by inhibiting MMP-9 secretion, epithelial-mesenchymal transition, and the Akt signaling pathway.…”
Section: Introductionmentioning
confidence: 99%